SST Cooling in the Indonesian Seas - Riza Yuliratno Setiawan; Abdullah Habibi (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2010)
Using advance satellite-derived sea surface temperature (SST) and sea surface wind, the characteristics of SST and wind variations in the internal Indonesian Seas (hereafter INA) were investigated. The seasonal cycle of SST in the INA is marked by a cooling in the dry season. The cooling, which occurs during May–August, is maximum in the eastern INA and decreases towards west. This study indicated that the southeasterly monsoon winds play a signicant role in the cooling phenomena in Indonesian Seas. The cooling is first identified in May, while August is its mature phase and it is affected by stronger winds (7-8 m/s) during July. An area with SST lower than 26°C appears in the Banda Sea, representing the coolest region in the INA. The results of the present investigation inferred that SST cooling in the INA is caused by southeast monsoon winds-ocean interaction. Key words: satellite remote sensing, SST cooling, southeast monsoon winds. Menggunakan satelit pemantau suhu permukaan laut (SPL) dan angin permukaan laut telah dikaji karakteristik dari SPL dan angin permukaan laut di perairan Indonesia. Siklus musiman SPL di perairan Indonesia dicirikan dengan “pendinginan” selama musim panas. Pendinginan, yang terjadi dari bulan Mei sampai Agustus, maksimum di perairan Indonesia timur dan minimum di perairan Indonesia barat. Studi ini mengindikasikan bahwa angin monsoon dari arah tenggara berperan penting dalam fenomena pendinginan di perairan Indonesia. Pendinginan pertama kali muncul di bulan Mei dan mencapai maksimum di bulan Agustus. Pendinginan tersebut disebabkan oleh pengaruh angin monsoon yang sangat kuat di bulan Juli. Area dengan SPL di bawah 26°C tampak di Laut Banda, dimana merupakan perairan yang paling dingin di Indonesia. Hasil penelitian menyimpulkan bahwa pendinginan di laut Indonesia disebabkan oleh interaksi angin monsoon tenggara dengan laut. Kata kunci: satelit penginderaan jauh, pendinginan suhu permukaan laut, angin monsoon tenggara